Energy partitioning on intermolecular interactions: ab initio Monte Carlo study of water dimer - Amano, T.; Sato, H.; Sakaki, S. (Condensed Matter Physics, 2007)
Ab initio Monte Carlo computations were carried out on H₂O dimer system. By introducing the energy partitioning
scheme that we have developed recently, ab initio calculated H₂O–H₂O interaction can be analyzed
from the viewpoint of atom-atom interaction. The electronic polarization caused by the interaction and its
temperature dependence are also discussed. To our best knowledge, this is the first report on the thermal
distribution of electronic distortion energy assigned to a molecule. Виконанi ab initio Монте Карло розрахунки для H2O димерної системи. Вводячи розроблену ранiше схему роздiлення енергiї, ab initio розрахована взаємодiя H2O–H2O може бути проаналiзована з точки зору атом-атомної взаємодiї. Обговорюється електронна поляризацiя, обумовлена взаємодiєю, та її температурна залежнiсть. З точки зору наших вiдомостей, це є перше повiдомлення про термiчний розподiл електронної змiни енергiї, переданої молекулi.